2016
DOI: 10.1186/s12916-016-0711-6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the prognostic and clinical value of tumor-associated macrophages in adult classical Hodgkin lymphoma

Abstract: BackgroundThe prognostic significance of tumor-associated macrophages (TAM) in adult classical Hodgkin lymphoma (cHL) remains controversial. Here, we report a meta-analysis of the association of CD68 and CD163 infiltration on the clinical outcome of adult cHL.MethodsA comprehensive search to identify relevant articles was performed in PubMed, Embase, and Google Scholar on January 31, 2016. Using the fixed effect or random effects model of DerSimonian and Laird, hazard ratios (HR) or odds ratios (OR) with 95 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
74
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 45 publications
6
74
0
3
Order By: Relevance
“…Most solid tumours include a variety of immune cells such as regulatory T cells, myeloid‐derived suppressor cells and tumour‐associated macrophages (TAM) that can suppress CTL functions . Among these cells, TAM is one of the most abundant cell types in solid tumours and their infiltration into the tumour associates with poor prognosis in most solid tumours . Furthermore, macrophages isolated from mouse and human solid tumours can directly suppress T‐cell responses and NK cell cytotoxicity in vitro .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most solid tumours include a variety of immune cells such as regulatory T cells, myeloid‐derived suppressor cells and tumour‐associated macrophages (TAM) that can suppress CTL functions . Among these cells, TAM is one of the most abundant cell types in solid tumours and their infiltration into the tumour associates with poor prognosis in most solid tumours . Furthermore, macrophages isolated from mouse and human solid tumours can directly suppress T‐cell responses and NK cell cytotoxicity in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among these cells, TAM is one of the most abundant cell types in solid tumours 8 and their infiltration into the tumour associates with poor prognosis in most solid tumours. [9][10][11][12][13][14] Furthermore, macrophages isolated from mouse and human solid tumours can directly suppress T-cell responses 15,16 and NK cell cytotoxicity 17,18 in vitro. It is also reported that depletion of TAM enhances CD8 + Tcell-mediated antitumour immunity under treatment with chemotherapy in a mouse model of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The latter are calculated by integrating clinical‐radiological parameters, including disease stage and site, the number of affected nodal regions, the presence of bulky disease and B symptoms 4 . Recent studies have also suggested a prognostic role for serologic and molecular markers, such as platelet and white blood cell counts, ferritin and albumin levels, 4‐6 erythrocyte sedimentation rate (ESR), 7 tumor‐associated mutations and polymorphisms, 8,9 and features of the tumor microenvironment 10,11 . None of these markers has entered the clinical practice as yet.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent studies have also suggested a prognostic role for serologic and molecular markers, such as platelet and white blood cell counts, ferritin and albumin levels, 4-6 erythrocyte sedimentation rate (ESR), 7 tumor-associated mutations and polymorphisms, 8,9 and features of the tumor microenvironment. 10,11 None of these markers has entered the clinical practice as yet. The prognostic relevance of histology is also a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…High frequency of CD68+ TAM in HL biopsies has been correlated with poor overall survival. (1925) Immunosuppressive and pro-tumor macrophages have been defined as M2 type, as opposed to inactivated (M0) or anti-infection/tumor macrophages (M1). (2628) Thus, HL represents a unique opportunity to study the impact of the TME on immunotherapy.…”
Section: Introductionmentioning
confidence: 99%